Pengelolaan Bumdes Hanjak Maju Dalam Berkontribusi Pada Pendapatan Asli Desa di Desa Hanjak Maju Kecamatan Kahayan Hilir Kabupaten Pulang Pisau - Irwani Irwani; Bahriannor Bahriannor (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Village-Owned Enterprises (BUMDes) are village business institutions that are managed by the community and village government in an effort to increase village finances and arrange village needs and potential. A Qualitative Research was conducted to find out how the management of Hanjak Maju BUMdes in contributing to the original village income in the village of Hanjak Maju, Kahayan Hilir District Pulang Pisau District. BUMDes Hanjak Maju has business unit FFB a palm oil, 3 kg gas and fertilizer business unit.The total revenue of Hanjak Maju PAD with an average production of FFB per month is 100 tons, then in the total production of FFB Hanjak Maju Village reaches 1,200 tons. Efforts to strengthen BUMDes Hanjak Maju should be done by encouraging the synergy of the Village Government,Village Consultative Body and village community to know the strategic position of the business unit developed by BUMDes, so as to foster active participation of all components of the village community